Analisis Kendala dan Solusi Peningkatan Pembelajaran PAI melalui Penggunaan Microsoft PowerPoint - Nurlisa, Nurlisa; Setiawati, Beti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This research aims to understand students' preferences regarding the use of PowerPoint in Islamic Religious Education (PAI) and to identify potential challenges. The 3D development paradigm is employed, with the